1992
DOI: 10.1002/elan.1140040802
|View full text |Cite
|
Sign up to set email alerts
|

Fast pulsed amperometric detection at noble metal electrodes: A study of oxide formation and dissolution kinetics at gold in 0.1 M NaOH

Abstract: The anodic charge (9) for oxide formation, obtained by potential-step chronocoulometry at a Au minidisk electrode, is nearly a linear function of log (t/ms> for t = ca. 3-30 ms with a slope proportional to the applied overpotential for oxide formation. It was demonstrated that, contrary to popular opinion based on voltammetric observation at slow scan rates ($1, the anodic current for oxide formation obtained using a linear potential-scan waveform is not a linear function of + at large values of + . It was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Similar developments were revealed by Johll et al [23] with the application of APAD for the detection of cysteine at Pt electrodes. However, future investigations by Roberts and Johnson [24] revealed oxide formation was not impeded completely by the reverse application of potentials at the Au electrode. The length of time in which oxide formation ceased was generally not enough for optimal detection conditions and in addition, the consumption of oxide during analyte detection resulted in varying background signal.…”
Section: Historical Developments Of Pedmentioning
confidence: 96%
See 1 more Smart Citation
“…Similar developments were revealed by Johll et al [23] with the application of APAD for the detection of cysteine at Pt electrodes. However, future investigations by Roberts and Johnson [24] revealed oxide formation was not impeded completely by the reverse application of potentials at the Au electrode. The length of time in which oxide formation ceased was generally not enough for optimal detection conditions and in addition, the consumption of oxide during analyte detection resulted in varying background signal.…”
Section: Historical Developments Of Pedmentioning
confidence: 96%
“…Roberts and Johnson [24,36] initially investigated oxide formation and dissolution kinetics at a Au electrode at basic pH in the anticipation of minimizing oxide growth to eliminate high background currents observed in Mode II detections. With their studies, Roberts and Johnson were able to deduce the origins of signal contribution as a result of surface oxide formation and dissolution.…”
Section: Faster Waveformsmentioning
confidence: 99%
“…The potential for reductive reactivation (Ered) was chosen to be -0.5 V and was applied for a period (tred) of 60 ms. Whereas the prior kinetic study [5] from current overload as a consequence of large current spikes. The total waveform period (TtOt) was the sum of the seven component time periods.…”
Section: Pad Waveformmentioning
confidence: 99%
“…Unfortunately, the ultimate rate at which PED can be performed is limited by the rate at which oxide can be formed and removed from the electrode surface. Roberts and Johnson [25,26] have speculated on the consequence of increasing the frequency of PED waveforms above the optimal value of 1 Hz prescribed for by HPLC-PED. They studied the kinetics of the oxide-formation and dissolution processes at Au electrodes in 0.1 M NaOH and concluded that only 20 ms is required for generation of a monolayer of AuOH at E oxd as the intermediate product in the anodic formation of surface oxide (AuO).…”
mentioning
confidence: 97%
“…The Johnson group [25,26] has proposed that the upper frequency of PED waveforms is limited by the slow kinetics of oxide formation and dissolution at Au and Pt electrodes, and the upper frequencies have been theorized to be ca. 15 Hz.…”
mentioning
confidence: 99%